2018
DOI: 10.1002/ijgo.12605
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contraceptive counselling training among counsellors participating in the FIGO postpartum intrauterine device initiative in Bangladesh

Abstract: Structured training had no impact on overall PPIUD insertion rate. However, it did impact numbers of women receiving counselling, perceived quality of the counselling received, and overall removal rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
(7 reference statements)
0
13
0
1
Order By: Relevance
“…Physician counselling was associated with higher satisfaction in a RCT in the USA,69 but did not increase postpartum use in Turkey,70 compared with leaflet/video counselling. Refresher provider trainings in Bangladesh71 and intensive counselling in Kenya72 were not associated with postpartum IUD uptake, continuation, or satisfaction.…”
Section: Resultsmentioning
confidence: 88%
“…Physician counselling was associated with higher satisfaction in a RCT in the USA,69 but did not increase postpartum use in Turkey,70 compared with leaflet/video counselling. Refresher provider trainings in Bangladesh71 and intensive counselling in Kenya72 were not associated with postpartum IUD uptake, continuation, or satisfaction.…”
Section: Resultsmentioning
confidence: 88%
“…20,[38][39][40][41][42][43][44] In 17 studies, the women's sociodemographic characteristics were described, including factors such as age, education, parity, number of living children and marital status. 17,18,[20][21][22][23][24]27,29,32,35,37,[39][40][41][42]44 Our primary outcome of interest, end-use of LARC, was reported in all 28 included studies, and was measured as (1) change in uptake of LARC -including number of women choosing LARC to be their first method of contraception as well as women switching to LARC from a different method [18][19][20]24,25,[27][28][29][30][31][32][35][36][37][38][39][40][41][42][43][44] ; and (2) change in IUD uptake specifically -including postpartum intrauterine devices. …”
Section: Re Sultsmentioning
confidence: 99%
“…17,18,[20][21][22][23][24]27,29,32,35,37,[39][40][41][42]44 Our primary outcome of interest, end-use of LARC, was reported in all 28 included studies, and was measured as (1) change in uptake of LARC -including number of women choosing LARC to be their first method of contraception as well as women switching to LARC from a different method [18][19][20]24,25,[27][28][29][30][31][32][35][36][37][38][39][40][41][42][43][44] ; and (2) change in IUD uptake specifically -including postpartum intrauterine devices. 17,[21][22][23]26,33,34 No studies reported the number of unintended pregnancies at 12 months after initiating LARC use, and 15 studies reported the preferred LARC method among healthcare workers and women. 19,…”
Section: Re Sultsmentioning
confidence: 99%
“…La distribución de tareas entre matronas y enfermeras para la inserción del DIU resultó muy eficaz en la India 12 , Nepal 10 , Kenia 10 y Tanzania 13 , con un aumento de las tasas de aceptación y muy poca variación en las tasas de complicaciones. En Bangladés, la formación de personas no sanitarias como asesores ofreció ciertas ventajas, pero no tuvo el impacto previsto respecto a la aceptación del DIUPP 14 . Esto refleja la gran variedad de factores que intervienen en algunas culturas en las que la mujer no es la que toma las decisiones sobre su propia salud sexual y reproductiva.…”
unclassified